2018
DOI: 10.1590/1414-431x20177132
|View full text |Cite
|
Sign up to set email alerts
|

Maternal administration of cannabidiol promotes an anti-inflammatory effect on the intestinal wall in a gastroschisis rat model

Abstract: Gastroschisis (GS) is an abdominal wall defect that results in histological and morphological changes leading to intestinal motility perturbation and impaired absorption of nutrients. Due to its anti-inflammatory, antioxidant, and neuroprotective effects, cannabidiol (CBD) has been used as a therapeutic agent in many diseases. Our aim was to test the effect of maternal CBD in the intestine of an experimental model of GS. Pregnant rats were treated over 3 days with CBD (30 mg/kg) after the surgical induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…To take part in the frontline of research in these new areas, Brazilian groups articulated to create the National Institute of Science and Technology for Translational Medicine (INCT-TM), funded by the Brazilian National Council for Scientific and Technological Development ( CNPq ) ( 146 ). As a result of this network, we contributed with further evidence on the actions of CBD as a neuroprotector ( 147 ), an anti-inflammatory ( 148 , 149 ), and a drug able to increase sleep periods ( 150 ), among other properties ( 151 157 ).…”
Section: Contemporary Days: Cbd As a Compound With A Wide Spectrum Ofmentioning
confidence: 98%
“…To take part in the frontline of research in these new areas, Brazilian groups articulated to create the National Institute of Science and Technology for Translational Medicine (INCT-TM), funded by the Brazilian National Council for Scientific and Technological Development ( CNPq ) ( 146 ). As a result of this network, we contributed with further evidence on the actions of CBD as a neuroprotector ( 147 ), an anti-inflammatory ( 148 , 149 ), and a drug able to increase sleep periods ( 150 ), among other properties ( 151 157 ).…”
Section: Contemporary Days: Cbd As a Compound With A Wide Spectrum Ofmentioning
confidence: 98%
“…The effects of the administration of different concentrations of CBD were evaluated to establish a dose-response relationship, since the literature does not provide a consensus on the ideal dose for anti-oxidant and anti-inflammatory action. In previous studies, the doses tested varied from 1 to 30 mg, but none of them stood out as advantageous in relation to the others in this study (Aviello et al, 2012;Callejas et al, 2018;Cassol-Jr et al, 2010;Chen et al, 2016;Elbaz et al, 2015;Klein et al, 2018;Napimoga et al, 2009;Pan et al, 2009;Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…The anti-emetic action of this compound has been reported by several authors and related to the indirect activation of receptors associated with these stimuli (Rock et al, 2012;Rock & Parker, 2015). In a recent study published by Callejas et al, where the anti-inflammatory potential of CBD in rat intestinal disease was tested, the authors demonstrated a significant increase in body weight in the group treated with CBD compared with the others due to the reversal of the inflammatory process present (Callejas et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…10% hempseed diet was able to reduce Cyclooxygenase-2 (COX-2) levels in hypercholesteraemic rats [ 71 ] while CBD purified from hemp demonstrated anti-inflammatory activities in a gastrochisis rat model [ 70 ]. In human polymorphonuclear cells, standardised extract containing 5% CBD, <0.2% THC and 95% cannabis vegetal complex matrix demonstrated dose-dependent anti-inflammatory effects via suppression of polymorphonuclear leukocyte migration, reactive oxygen species (ROS) generation and TNF-α production [ 72 ].…”
Section: Resultsmentioning
confidence: 99%